International Technology Sourcing and Knowledge Spillovers : Evidence from OECD Countries - Chen, Sophia (IMF Working Papers; Working Paper ;, 2018)
How much do firms benefit from foreign R and D and through what channel? We construct a global network of corporate innovation using more than 1.5 million patents granted to firms in OECD countries. We test the 'international technology sourcing' hypothesis that foreign innovation activities tap into foreign R and D and improve home productivity through knowledge spillovers. We find that firms with stronger inventor presence in technology frontier countries benefit disproportionately more from their R and D. The strength of knowledge spillovers depends on the direction of technology sourcing. Knowledge externality is larger for firms in technology frontier countries than for firms in non-frontier countries.